EFEKTIVITAS PENGOLAAN DANA DESA DITINJAU DARI KUALITAS PELAPORAN KEUANGAN DESA DI DESA SUMBERSEKAR - Yuliana Sagitarini; Ahmad Mukoffi; Soko Wikardojo; Sukarno Himawan (Jurnal Magister Akuntansi Trisakti, 2022)
The purpose of this research is to determine the management of village funds on village financial reporting in the village of Sumbersekar and to determine the quality of village financial reporting in the village of Sumbersekar. This type of research is an interpretive qualitative method that is able to provide a rich picture of the context of the research, the process is interactive and by collecting data such as documentation and observation, as well as by collecting data from various sources which will be known as triangulation (combined), the type of data that is used. used are primary and secondary data, the source of data in this research is the source of data derived from informants. Data collection techniques are interviews, observation, documentation, and literature study, while the data analysis techniques used are a subject of various parts, the examination of the parts themselves and also the relationship between the sections in order to obtain a proper understanding and overall understanding of this research. Processing and data analysis using descriptive analysis. The results of the study can be stated that the effectiveness of village fund management in terms of the quality of village financial reporting in Sumbersekar Village is declared effective, because financial management through village expenditure targets is higher than expenditure realization, the effectiveness of village fund management in 2017 was 96.92%, in 2018 it was 98.04 % whereas in 2019 it was declared quite effective because the realization of village expenditure was higher than the village expenditure target of 104.32%, as well as the effectiveness of village fund management if the village expenditure target was higher than the realization of village expenditure, it was said to be effective. Meanwhile, if the management of village funds in the realization of village spending is higher than the target of village expenditures, it is said to be quite effective